Faktor Yang Mempengaruhi Perkembangan Perumahan Swasta Du Kota Padang - Putri, Agisti Amelia; Fosterharoldas, Deva; Roychansyah, Sani (Fakultas Teknik, Universitas Brawijaya, 2018)
Padang City is one of the coastal city located in coastal area of Sumatera Island. The beginning of the development of housing was in the western region which was the Muara Batang Arau Port Area. The development of private housing in the city of Padang continues to shift increasingly moving towards the eastern region which is a suburb far from the coast. This phenomenon affects the activities of large land conversion that resulted in changes in the structure of the Padang City space and increasingly eliminate the characteristics of the City of Padang as a Beach City. This is interesting to study so research questions arise as to the development of private housing in the city of Padang and what are the factors that influence this development. The purpose of this study is to describe the development of private housing in the city of Padang and identify factors that influence the development of private housing in the city of Padang. The research approach used is deductive qualitative rationality, which in the analysis phase uses a Geographic Information System (GIS) to describe the development of private housing in Padang City in 2007-2016.The results showed that there was a change in the orientation of private housing development from 2007-2016 from the western part of Padang Sarai, Lubuk Buaya, Pasie Nan Tigo, Bungo Padang and Parupuk Tabing villages to the eastern part of Balai Gadang Village, Lubuk Minturun Urban Village, Gunung Sarik Urban Village and Kuranji Village with the addition of 156 Ha of private housing area. Factors affecting housing development in Kota Padang are factors of policy, population factor, land limitation factor, and partnership factor.Keywords: Kota Padang, development of private housing, factors